Absorption spectra and nonlinear transmission (at ) of a diffusion-doped single crystal. (June 2015) - Bufetova, G.A.; Gulyamova, E.S.; Il'ichev, N.N.; Nasibov, A.S.; Pashinin, P.P.; Shapkin, P.V.
Abstract Transmission spectra of a ZnSe sample diffusion-doped with <?CDATA ${\text{Fe}}^{2+}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9508s8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> ions have been measured in the wavelength range <?CDATA $500 {-} 7000\ {\text{nm}}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9508tt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. A broad absorption band in the range <?CDATA $500 {-} 1500\ {\text{nm}}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9506ts" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> has been observed in both doped and undoped regions of the sample. This band is possibly due to deviations from stoichiometry in the course of diffusion doping. The transmission of the <?CDATA ${\text{Fe}}^{2+}:{\text{ZnSe}}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9508q5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> sample at a wavelength of <?CDATA $2940\ {\text{nm}}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9508rq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> has been measured at various dopant concentrations and high peak pulse intensities (up to <?CDATA $8\ {\text{MW cm}}^{-2}$?> <inline-graphic xlink:href="ark:/27927/pgj2c9505c3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />). The samples have been shown to be incompletely bleached: during a laser pulse, the transmission first increases, reaches a maximum, and then falls off. Our results suggest that the incomplete bleaching cannot be accounted for by excited-state absorption. The incomplete bleaching (as well as the transmission maximum) is due to the heating of the sample, which leads to a reduction in upper level lifetime and, accordingly, to an increase in absorption saturation intensity.